Using trip chaining and joint travel as mediating variables to explore the relationships among travel behavior, socio-demographics and urban form - Chen, Yu-Jen; Akar, Gulsah (Journal of Transport and Land Use, 2017)
Using the 2012 Household Travel Survey data for the Cleveland metropolitan area, this study aims to examine the connections between travel behavior by using trip chaining and joint travel as mediating variables of travel distances and controlling for socio-demographics and urban form. Trip chaining and joint travel capture the complexity of tours and intra-household interactions, respectively. Socio-demographics represent personal and household characteristics. Urban form, which is measured not only at tour origins but also at tour destinations, helps capture the effects of residential density, retail and non-retail densities, transportation connectivity, public transit accessibility, and land-use mix. Structural equation model (SEM) approaches are applied to examine the interrelationships among these variables. The model results reveal that significant effects with expected signs exist among travel behavior: Trip chaining is negatively associated with joint travel and positively related to travel distances, and joint travel has negative effects on travel distances. Consistent with existing literature, socio-demographic attributes are strong explanatory factors of travel behavior. Urban form characteristics have significant influence on travel distances at both tour origins and destinations. The findings of this study will improve the future evaluation of transportation projects and land-use policymaking.